Quality of Complaint Services through the Lapor Website at Departement of Education the East Java Provincial - Lia, Siti Noer; Tukiman, Tukiman (Borong Newinera Publisher, 2024)
The development of an Electronic Based Government System is an embodiment of improving the quality of public services. The LAPOR website is a national electronic-based complaint management system that can be accessed by all Indonesian people. The existence of LAPOR mandates that the management of complaint services in every government agency in Indonesia must be integrated with LAPOR, At department of east java provincial education service. The LAPOR website is the most widely used media by the people of East Java in sending complaints to at Departement of Eduaction The East Java Provincial. However, in reality there are still some complaints from the public about the services provided through LAPOR website. The purpose of this research to determine the quality of complaint services through the LAPOR website at Departement of Education The East Java Provincial. This research uses a qualitative approach with data collection techniques through observation, interview, and documentation. The results showed that the quality of complaints service through the LAPOR Website using the four objectives of the Electronic Service Quality theory study was of high quality but not optimal, because there were still several complaints whose follow-up did not run optimally and there were several complaints that experienced delays in the follow-up of further complaints.